Green Finance and Sustainability: A Systematic Review - Wahyudi*, Arif; Triansyah, Fadli Agus; Acheampong, Kennedy (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2023)
This research aims to explore and analyze the recent focus on green finance and sustainability from 2022 to 2023. It employs a systematic review approach to understand the predominant areas of study during this two-year period. The data search revealed that research focusing on the impact of green finance on decarbonization has gained significant popularity in the past two years. Additionally, other studies have delved into various variables such as Environmental (Management, Economics, Performance, and sustainability), Technology (AI, Blockchain, Smart, and adoption), and Renewable Energy & its Output. This research primarily concentrates on topics that have emerged as trends in the last two years. However, it's noteworthy that among these studies, there are 14 research topics that have been explored less frequently. These include Green Financing, Insurance, Non-Performing Loan Ratio, Ecological Footprints, Climate Mitigation Finance, Solvency, Biofuel, Fuel Cell, Geothermal, Solar, and Wind. Keywords: Green Finance; Sustainability; Systematic Review; Economics; Environmental